2013
DOI: 10.4995/wrs.2013.1173
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of male rabbits of algerian local population

Abstract: A total of 267 rabbit does and 46 bucks from a local Algerian population were controlled during 6 generations (from G0 to G5) at the experimental farm of the University of Tizi-Ouzou. Natural mating was used and 1412 presentations were analysed. Reproductive and growing performance were analysed taking into account the effect of the buck, its age, the generation, the season of mating (or kindling) and the physiological status of does at the moment of the mating. The buck influenced the acceptance rate (P<0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Also, they had significantly lower fructose level (201.32 mg/dl) than those recorded in the old age (245.66 mg/dl), but not significant with the young age (22.98 mg/dl). The results are in agreement with Cherfaoui et al (2013), who recorded that age of male affected aversely semen characteristics in rabbit. In fact, degradation of semen quality with the increase of male age leads to decrease in fertility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, they had significantly lower fructose level (201.32 mg/dl) than those recorded in the old age (245.66 mg/dl), but not significant with the young age (22.98 mg/dl). The results are in agreement with Cherfaoui et al (2013), who recorded that age of male affected aversely semen characteristics in rabbit. In fact, degradation of semen quality with the increase of male age leads to decrease in fertility.…”
Section: Discussionsupporting
confidence: 92%
“…Mahmoud et al (2013) found that combination of Vitamin E and selenium improved semen characteristics and the reproductive performance in Ossimi rams. It is well known that semen quality is reduced with increasing age of rabbit bucks, because of degradation of semen quality with increasing age lead to decrease in fertility, conception rates and the productivity of the does (Cherfaoui et al, 2013). Also, Tanemura et al (1993) reported that there was narrowing and sclerosis of the tubular lumen, a decrease in spermatogenic activity, degeneration of germ cells, and decreased number and function of Leydig cells with increasing age of male mouse.…”
Section: Introductionmentioning
confidence: 99%